Foreign direct investment,trade openness,and economic growth: empirical evidence from Thailand - Yusoff, Mohammed; Nuh, Ruslee (Sage Publications, 2015)
In recent years, the Thailand’s economy has become more open to foreign trade as well as foreign direct investment(FDI). Thus the main objective of this study is to examine whether FDI and international trade have positively contributed to the economic growth of Thailand. The results of the Granger causality tests indicate that they are indeed important determinants of growth in Thailand. This suggests that policy makers in Thailand should liberalize its economy to encourage foreign trade and foreign direct investment inflows to achieve a sustained high economic growth.